Analysis of correlation of socio-economic status, demographic parameters and clinical parameters in pregnant womens, who were attending a tertiary care rural hospital - K. Kameswaramma (Asian Pacific Journal of Health Sciences, 2014)
Background: Pregnancy is associated with normal physiological changes that assist the nurturing and survival of the fetus. Various factors involve in this context, like biochemical, hematological, socioeconomic etc. Objective: present study, designed to assess sociodemographic data and clinical data in normal pregnant women in rural area of Nellore District. Methodology: A case-control study comprised 100 womens, comprised 50 pregnant womens and 50 healthy non pregnant age-matched controls carried out at Dept. of Gynecology & Obstetrics, Narayana Medical College Hospital, Nellore Rural, Andhra pradesh. Data related to sociodemographic data (age, education, employment and family income/month), medical history (previous pregnancy complications), clinical data (complication during this pregnancy, treatment and blood pressure), and food and drink intake were collected by the questionnaire and analyzed. Results & conclusion: Unemployment women and lower family income were more prevalent among pregnant women. Medical history of the study population showed that the frequency of the previous pregnancy in controls was significantly lower than that in cases. In general, blood pressure of the study population was within the normal range. The food and drink intake observation showed that pregnant women ate less fish and egg and more fruits and vegetabl) than non pregnant women. Coffee was drunk more frequently by non pregnant women. Hence, Poor food and drink regime observed among pregnant women necessitate the presence of healthy food program in the antenatal care clinics. In this context, consumption of fruits along with the main meals of all women in reproductive age should be reinforced. Frequent monitoring of blood pressure throughout pregnancy should be advised.